State of the world 2017: autocratization and exclusion?. Issue 8 (17th November 2018) - Lührmann, Anna; Mechkova, Valeriya; Dahlum, Sirianne; Maxwell, Laura; Olin, Moa; Petrarca, Constanza Sanhueza; Sigman, Rachel; Wilson, Matthew C.; Lindberg, Staffan I.
ABSTRACT: This article presents evidence of a global trend of autocratization. The most visible feature of democracy – elections – remains strong and is even improving in some places. Autocratization mainly affects non-electoral aspects of democracy such as media freedom, freedom of expression, and the rule of law, yet these in turn threaten to undermine the meaningfulness of elections. While the majority of the world's population lives under democratic rule, 2.5 billion people were subjected to autocratization in 2017. Last year, democratic qualities were in decline in 24 countries across the world, many of which are populous such as India and the United States. This article also presents evidence testifying that men and wealthy groups tend to have a strong hold on political power in countries where 86% of the world population reside. Further, we show that political exclusion based on socio-economic status in particular is becoming increasingly severe. For instance, the wealthy have gained significantly more power in countries home to 1.9 billion of the world's population over the past decade.